Perioperative nursing based on enhance recovery after surgery for pediatric patients undergoing modified artificial partial knee-joint prosthesis replacement for osteosarcoma around the knee joint (儿童膝关节周围骨肉瘤改良人工半膝关节假体置换围手术期的快速康复护理) - NONG Yuanxia (农源夏); CHEN Jian (陈剑); YANG Shuyun (杨舒云) (中西医结合护理)
This paper investigate the effect of enhance recovery after surgery (ERAS) in perioperative nursing of pediatric patients undergoing modified artificial partial knee-joint prosthesis replacement for osteosarcoma around the knee joint. The clinical data of 8 pediatric patients with osteosarcoma around the knee joint were retrospectively analyzed. Based on the concept of ERAS, enhanced health education, nutrition support and psychological care were carried out before surgery. In addition to routine postoperative nursing, efforts were made to improve the positioning management, function exercise and prevention of postoperative complications. All pediatric patients were followed up and recovery with good walking posture. ERAS-based nursing intervention is effective to improve the functional recovery of knee joint and reduce the postoperative complications in modified artificial partial knee-joint prosthesis replacement for osteosarcoma around the knee joint. (本文探讨快速康复护理模式在儿童膝关节周围骨肉瘤改良型人工半膝关节假体置换手术围手术期护理中的应用效果。回顾性分析2018年1月—2019年12月医院收治的8例膝关节周围骨肉瘤患儿的临床资料。遵循快速康复理念, 术前加强围手术期健康宣教、营养支持和心理干预; 术后在常规护理基础上, 完善体位护理、功能锻炼和并发症预防。出院后随访, 患儿步态良好, 基本满足日常生活需求。基于快速康复护理理念的护理干预能够促进患儿膝关节功能恢复, 减少术后并发症, 提高患儿生活质量。)